2023
DOI: 10.14745/ccdr.v49i06a03
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the economic gains associated with COVID-19 vaccination in the Canadian population: A cost-benefit analysis

Abstract: Background Vaccination has been a key part of Canada’s coronavirus disease 2019 (COVID-19) pandemic response. Although the clinical benefits of vaccination are clear, an understanding of the population-level benefits of vaccination relative to the programmatic costs is of value. The objective of this article is to quantify the economic impact of COVID-19 vaccination in the Canadian population between December 2020 and March 2022. Methods We conducted a model-based cost-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“… 61 Estimates of incidence from the United States, accounting for underreporting, are those obtained with the implementation of efforts to prevent LD. Recent studies identified the high economic impact of a vaccine for COVID-19 when compared with counterfactual scenarios, 62 which underlines the potential importance of the development of an effective vaccine against LD. It also underlines, in the absence of a vaccine, the importance of efforts to prevent early LD cases (by, e.g., increasing public and physician awareness) becoming disseminated cases, for which the personal costs to the well-being of patients, and the economic costs are much greater.…”
Section: Discussionmentioning
confidence: 99%
“… 61 Estimates of incidence from the United States, accounting for underreporting, are those obtained with the implementation of efforts to prevent LD. Recent studies identified the high economic impact of a vaccine for COVID-19 when compared with counterfactual scenarios, 62 which underlines the potential importance of the development of an effective vaccine against LD. It also underlines, in the absence of a vaccine, the importance of efforts to prevent early LD cases (by, e.g., increasing public and physician awareness) becoming disseminated cases, for which the personal costs to the well-being of patients, and the economic costs are much greater.…”
Section: Discussionmentioning
confidence: 99%